2020
DOI: 10.1029/2020gl088421
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Roles of High Harmonics on Interactions Between AKR and Radiation Belt Relativistic Electrons

Abstract: Auroral kilometric radiations (AKR) are widely existing superluminous waves in the magnetosphere. Due to rarely available measurements of AKR magnetic field components, we derive the explicit expression of diffusion coefficients in terms of electric field components, which can be applied to various space plasma waves. Using Van Allen Probes data, we calculate diffusion coefficients with different harmonic orders for two AKR events. It is found that the first (higher) harmonic order contributes to diffusion coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In addition, if the PSD of wave magnetic field and electric field are chosen to follow the same frequency distribution, the empirical formula of AKR magnetic field amplitude can be obtained based on the Maxwell’s equations and Equation . However, considering that the Arase satellite and Van Allen Probes currently provide only the electric field PSD of AKR emissions in the radiation belts, we prefer to use formulas in terms of AKR wave electric field amplitude to calculate diffusion coefficients (Zhang et al., 2020). The concise formula probably provides a very useful method to model AKR‐electron interaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, if the PSD of wave magnetic field and electric field are chosen to follow the same frequency distribution, the empirical formula of AKR magnetic field amplitude can be obtained based on the Maxwell’s equations and Equation . However, considering that the Arase satellite and Van Allen Probes currently provide only the electric field PSD of AKR emissions in the radiation belts, we prefer to use formulas in terms of AKR wave electric field amplitude to calculate diffusion coefficients (Zhang et al., 2020). The concise formula probably provides a very useful method to model AKR‐electron interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, their studies are limited within low latitudes due to the low latitude orbit of Van Allen Probes. Various studies (Summers et al., 2001; Xiao, Chen, He, 2010; Xiao et al., 2006; Xiao, Su, et al., 2010; Zhang et al., 2020) have found that the AKR has a potential for producing acceleration (or precipitation) of electrons in radiation belts under appropriate conditions. The aforementioned acceleration or loss of energetic electrons can yield serious damage to spacecraft by surface charging (Baker, 2002) or ozone destruction via chemistry change in atmosphere (Thorne, 1977; Callis et al., 1998; Thorne et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that wave‐particle interaction is an important process of magnetosphere‐ionosphere‐atmosphere coupling and has been studied widely by researchers (Q. Yang et al., 2016; Jin et al., 2018; Guo et al., 2020; Guan et al., 2020; C. Yang et al., 2021; He et al., 2021). Various studies have proved that AKR can produce efficient acceleration or pitch angle scattering of energetic electrons under appropriate conditions (Summers et al., 2001; Xiao, Chen, & He, 2010; Xiao, Chen, He, & Yang, 2010; Xiao et al., 2006; Xiao, Su, et al., 2010; Zhang et al., 2020). Those accelerated or scattered electrons can cause ozone destruction or serious damage to spacecrafts (Baker, 2002; Callis et al., 1998; Thorne, 1977; Thorne et al., 2005).…”
Section: Introductionmentioning
confidence: 99%